Dolomitisation and brecciation along fault zones in the Cantabrian mountains - Grimmer, Jörg O. W.; Bakker, Ronald J.; Zeeh, Stefan; Bechstädt, Thilo (Journal of geochemical exploration, 2000)
Dolomitisation, brecciation, and dedolomitisation occurring in fault zones in the Variscan fold and thrust belt in the Cantabrian Zone (Northern Spain) in three different tectonic units (Ponga, Picos de Europa and Esla) have been investigated and compared. Cementation patterns are similar in all units: dolomite cements always predate calcite cements in brecciated limestone (Barcaliente Fm.). Moreover, carbon and oxygen isotopic composition trends are comparable. However, the precipitating fluids are distinct in each fault zone, as evidenced by microthermometry and Raman spectroscopy. The evolution of the fault zones is illustrated by the precipitation of cements from different types of circulating fluids in several pulses.